Optimizing Pesantren-Owned Enterprises (BUMP) as Halal Business Incubators: Promoting Economic Independence for the Community - Sutantri; Stevanus Gatot Supriyadi (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose – This study aims to formulate a framework for optimizing BUMP through structural transformation into a Halal Business Incubator (IBH). Design/Methods/Approach – The methodology employed is a conceptual, prescriptive, and descriptive qualitative approach, synthesizing governance, incubation models, and Sharia funding architecture. Findings – Pesantren-owned enterprises (BUMP) hold a strategic position as an anchor for the Muslim community's economy and a key instrument in realizing Indonesia's vision as a Global Halal Hub. However, there are significant challenges, particularly in terms of human resource capabilities, literacy in halal development instruments, and limited access to capital. Research Implications/Limitations – The analysis resulted in the Four Pillars Optimization Model: (1) Strengthening Centralized Relational Governance for accountable and digital supervision; (2) Five Pillars Integrated Halal Incubation Operational Model that places Halal Assurance at its core; (3) A Strategy for Strengthening Human Resource Capabilities through massive halal literacy training; and (4) A Sharia Blended Finance Funding Architecture that synergizes Productive Waqf for assets and Shariah Crowdfunding for working capital. Originality/Value – This research provides an optimization roadmap for BUMP to improve the competitiveness of MSMEs by accelerating halal certification and fundamentally promoting independence.